Responsibilities And Notary Law As A Legal Consultant - Reidha Novyca Putri N.S; Habib Adjie (Faculty of Law, Merdeka University Surabaya, 2020)
Notary is a public official with the authority to make authentic deed as strong evidence. In the process of making an authentic deed, the client needs advice about legal actions that will be recorded in the authentic deed, this is referred to as legal consulting services by a notary. In practice found a notary as a legal consultant with the inclusion in a separate sign in the notary's office. The purpose of this study is to examine the actions of a notary as a legal consultant. This research method uses a normative juridical method with a conceptual approach and legislation. The conclusion of this research is that the act of installing a signboard as a legal consultant is an unjustified act and the notary can be held accountable for the results of the consultations given.